The valve-sparing aortic root replacement: Results of the David I technique - B. M. Todurov; I. O. Stetsyuk; O. V. Zelenchuk; I. Yu. Mokryk; L. R. Stetsiuk; V. B. Demyanchuk; N. V. Malova (Кардіохірургія та інтервенційна кардіологія)
The aim – to determine the long-term results and quality of life of patients who underwent David І valve-sparing operation. Materials and methods. The one-center study included 53 patients who underwent planned and urgent David I procedure (valve-sparing replacement of the aortic root and ascending aorta) from 2015 to 2023. The mean age of the 53 patients (among them, 47 (88.68 %) males) was 49.11 ± 1.54 years. We analyzed basic characteristics of the patients, intraoperative and postoperative data. The quality of life was assessed before and in the long-term period after operations by the Medical Outcomes Study Short Form 36 (MOS SF-36) questionnaire. Results and discussion. An average duration of the follow-up period was 2.59 ± 0.27 years ranging from 1.0 to 9.0 years. Overall in-hospital mortality and 30-day mortality was 1.89 % (n 1). Estimated 5-year survival rate was 95.7 ± 1.45 % for all patients. The average duration of the operations was 291.23 ± 12.67 minutes, the total duration of artificial blood circulation was 170.28 ± 8.77 minutes, aorta clamping time – 122.02 ± 5.92 minutes. The mean duration of stay in the hospital was 13.81 ± 0.54 days, intensive care unit – 2.94 ± 0.03 days. The number of patients extubated up to 8 hours after surgery was 48 patients (90.57 %). The performed operation significantly improved the indicators. Patients positively perceived the information about the absence of an artificial heart valve and need of concomitant use of anticoagulants. The patients had a good psycho-social component, which probably affected the assessment of other scales. Conclusions. Patients after David I operation have a low overall in-hospital mortality and 30-day mortality, with a short period of time in intensive care unit and hospital at all. Long-term results in indicator of 5-year survival are excellent. The operation significantly improves quality of life parameters.